CHARACTERISTICS OF TUNA, SMALL TUNA AND SKIPJACK (TTS) FISHERY IN KUTARAJA OCEAN FISHING PORT, ACEH - Gussasta Levi Arnenda; Fathur Rochman (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2021)
Kutaraja Ocean Fishery Port is the oldest port in Banda Aceh City, Lampulo. Fishery resources are a new potential in the regional economic development of Aceh province. Fish resources that have great potential are from the large pelagic fish groups, including Tuna, Small Tuna and Skipjack (TTS) . Fishery characteristics are used to carry out sustainable fishing. This research was conducted at PPS Kuta Raja, Aceh for one year. Data collection was carried out directly through site surveys and interviews with related fisheries actors. Biological data and capturing aspects were carried out using a stratifield random sampling system by placing enumerators. The results showed that the production of TCT at PPS Kutaraja was dominated by 2 fishing gears, purse seine and hand lines. Based on the results of enumeration in 2020, the estimated total production of tuna skipjack and small tuna at PPS Kuta Raja reaches 11,520 tons. The highest total estimated fish catch is skipjack tuna (Katsuwonus pelamis) (SKJ) 5,802 tons, Bullet tuna (Auxis rochei)(BLT) 2814 tons, Yellow fin  (Thunnus albacares) (YFT) 2,452 tons, Krai Tongkol (Auxis thazard) (FRI) 448 tons, and Eastern little tuna (Euthynnus affinis) (KAW) 1,745 tonnes. All of the fish caught were dominated by immature fish. So it is very necessary to evaluate the use of fishing gear or the licensing of FADs. The monthly CPUE distribution pattern is the same, where in August it reaches the highest CPUE and in October it reaches the lowest CPUE value.